Can Disadvantaged Kids Ever Catch Up with Better-off Peers? - World Bank (Washington, DC, 2013)
The World Bank is focused on developing and supporting programs that help children reach their potential and live lives free of poverty. To help build a body of evidence of what works, the World Bank financed an evaluation of a program in Jamaica that targeted mothers of babies stunted due to malnutrition. The mothers received either support or guidance on how to encourage their babies' development through play and language, or nutritional supplements, or a combination of the two. The children whose mothers had received the extra guidance were doing as well financially as the less disadvantaged (and non-stunted) children. This study is a rare look at the effects of early childhood intervention over the decades, giving policymakers and development experts tangible proof of the potential effects of early childhood development programs. A rare long-term study of the effects of an early childhood development program shows that children's lives can be improved by ensuring that they have the right stimulation and emotional support as babies and toddlers.